Numerical and Experimental Modal Analyses of Inclined Supported Bridge Wing Structures - Yucel, Adil (International Institute of Acoustics and Vibration (IIAV), 2022)
This paper studies ship bridge extensions called "bridge wings", which are one of the most critical areas of importance in ship vibration. These extensions, which have been modeled at the laboratory scale, have been analyzed using both experimental and finite element analysis methods. Bridge wing models have been constructed with varying inclination angles, and the natural frequencies and mode shapes obtained, both experimentally and numerically, have been compared. In this way, the effects of design properties on the results have been emphasized. Besides, the natural frequency discrepancies between the experimental and finite element analyses have been found to be very low. Another important result of this study has been obtained such that a certain support angle has been detected which the mode shape transition occurs in resonance. Natural frequency and mode shape analyses of the plates which have been supported with beams with varying inclination angles and achievement of mode shape transition phenomenon can be considered as the novelty about the contribution of this study to the state-of-the-art.